Public service innovation process of smart kampung program at Banyuwangi - Choirul Saleh; Ibad, Syahrul; Mindarty, Lely Indah; Hariyono, Bambang Santoso (Jurnal Studi Komunikasi, 2023)
This study aims to describe and analyse the process of public service innovation through the Smart Kampung Banyuwangi program. The emergence of various qualified public service innovations is the main indicator of responsiveness in community services. This research has a qualitative method study, based on the analysis of the public innovation process of "Smart Kampung Banyuwangi" conducted within the local government of Banyuwangi, East Java, Indonesia. The findings show that the public service innovation process of "Smart Kampung Banyuwangi" was done systematically and comprehensively so the Program has properly. This study concludes that the Smart Kampung Banyuwangi program has a positive and significant impact on solving problems in rural areas, as well as producing optimal performance in providing public services to rural communities because people can get services that are faster, closer, more precise, easier, cheaper and more other advantages.